ESG Practices, Maqāṣid al-Sharī‘ahOrientation, and Sustainable MSME Performance: Evidencefrom Pekanbaru, Indonesia - Hidayat; Khodijah Ishak; Zulhelmy; Hamsal; Nasya Adila (LPPM ISNJ Bengkalis, 2026)
Purpose–This paper examines the role of Environmental, Social, and Governance (ESG) practices on Maqāṣid al-Sharī‘ah orientation and SMEs sustainable performance in a developing economy. Additionally, it also aspires to combine sustainability practices with Islamic ethical principles in the SME context. Method: This study used quantitative methodology by conducting a cross-sectional survey with 400 owners and managers of SMEs in Pekanbaru, Indonesia. The collected data were analyzed based on the Partial Least Squares Structural Equation Modeling (PLS-SEM) method running through Smart-PLS. The conceptual framework explores influences of ESG practices on Maqāṣid al-Sharī‘ah orientation and, in turn, the effect that Maqāṣid al-Sharī‘ah orientation has on sustainable SME performance. Findings: The analysis shows that environmental, social and governance practices have a positive impact on Maqāṣid al-Sharī‘ah orientation with the highest influence being associated with governance amongst all three aspects. Maqāṣid al-Sharī‘ah orientation also has a positive impact on sustainable SME performance. Implications: The findings highlight that ESG practices in SMEs go beyond technical sustainability initiatives, reflecting ethical business conduct guided by the principles of trusteeship, justice, accountability and public benefit.